Psychological and Social Problems of Adult Female Victims After Sexual Assault - Gölge, Zeynep Belma; Yavuz, Mustafa Fatih; Korkut, Songül; Kahveci, Sevilay (The Bulletin of Legal Medicine, 2014)
Objective: This study aimed to investigate the prevalence of psychological and social problems faced by female victims after rape and additionally the impact of also being a victim of childhood sexual abuse in Turkey, where opportunity of getting medical and psychological support for sexual assault for victims is limited and legal process lasts for years. Method: Participants consisted of 93 female rape victims who were examined by the Second Specialization Board of State Council of Forensic Medicine. An interview form, which is developed in order to investigate socio-demographic features, assault charactersitics, psychological and social problems of victim, Post Traumatic Diagnostic Scale (PTDS) and Childhood Trauma Questionnaire were applied for the investigation. Results: 61.3 % of victims were diagnosed with post traumatic stres disorder (PTSD) and 54.8% of victims had sexual dysfunctions caused by the sexual assault. 68.8 % of victims reported that they were exposed to negative social reactions. 70,3% of victims who were exposed to negative social reactions met diagnostic criteria for PTSD while only 41,4% of people who were not exposed to negative social reactions met diagnostic criteria for PTSD. Difference between groups was analyzed with chi squre method and there is significant difference between them ( X2:7.04, df:1, p<0.01). Self-mutilation and suicide attempts were high in victims of adult rape who were also sexually abused in childhood. Discussion: Considering duration between the sexual assault and interview, in our research findings the ratio of the people who have PTSD and sexual issues, is more than the other studies consequences. On the other hand, the victims which reported that incident occured more than three years ago, are fitted to the diagnosis criterias of PTSD, with the ratio of 58.8%. It’s been thought that, studying with the victims who has been sent for physical examination and the continuation of judicial process are both have impact on this conclusion. Key Words: Rape, trauma, PTSD, self mutilation